ECONOMIC THEORY OF RATIONALIZATION CONSUMPTION OF HOMES & HOTELS WITH INSTRUCTIONS OF TEXTILES AND APPAREL CARE LABELS - ELNASHAR, Elsayed Ahmed (Herald of Khmelnytskyi National University. Economic sciences, 2023)
Economic theory of rationalization consumption and the wear-life of textiles and apparels depend on the care one takes of them. Long before house and hotel laundry operators could easily identify from natural raw materials such as a wool or cotton textiles and apparel, synthetic materials such as nylon, polyester and acrylic used in clothing, homes and hotels, and successfully clean it without a care label. Rationalization consumption with new fibers and new technology has created a vast array of textiles and apparel. Unfortunately, house and hotel laundry operators had no way of knowing just how to properly clean these textiles and apparels. Rationalization consumption in such situation care labels plays an important role. Care labels indicate how to clean textiles and apparel in best possible way and provide the necessary information about their washing, bleaching, ironing and dry-cleaning of textiles and apparels. Thus the present study was conducted for enhancing the knowledge of house and hotel laundry operators. the results of the study reveals that the existing knowledge of rationalization consumption that the house and hotel laundry operators regarding textiles and apparel labels, label placement and forms of care instruction was good but, with respect to textiles and apparel care symbols, all the respondents possessed poor knowledge. After the training the knowledge was found to be good. Knowledge gain was found significant regarding textiles and apparel care labels.